КАФКА, ХУМОРИСТ (Philological Studies, 2019)
The most persistent reading of Kafka’s work identifies Kafka as an author of intimism (the Freudian nuclear family), nihilism (everything eventually amounts to the impossible exits from the unidentifiable and unfair Law), and pessimism. The study Kafka, the Humorist proposes that Kafka should be read as a humorist, for at least two reasons. 1) Kafka distanced himself from the bitter mode which dominated the 20th century interpretations of his work as pessimistic. The most amusing passages in Max Brod’s biography of Kafka are devoted to describing the humorous, clownish mode in which Kafka read parts of his novel Trial to the audience at Brod’s literary meetings in Prague, and the audience responds with an “unrestricted laughing”; 2) Reading Kafka as a humorist, rather than a pessimist, actually has a longer and also a more credible tradition. As early as 1934, Walter Benjamin in his study Kafka suggested jesting as the most adequate approach to Kafka’s work. Deleuze and Guattari following Benjamin's advice in their 1975’s book Kafka spoke about “a very joyful laughter” in Kafka, but also noted that this mode passed mainly unrecognized by Kafka's critics. Finally, David Foster Wallace in his review Laughing with Kafka from 1998 writes about the complexity of Kafka’s funniness, claiming that his humor has a “heroically sane” quality. The study Kafka, the Humorist tests the directions given by Benjamin, Deleuze and Guattari and Wallace, and tries to interpret the humor with regard to some of Kafka’s more frequent topics: animalism, miniaturization, asceticism; but also: children, food, knife, machines, to Kafka’s portraits of some of the more notorious figures of his time (among others, his commentaries about Charlie Chaplin and Benito Mussolini, which strike the reader with their unusual similarity).
Keywords: Franz Kafka, humor; Walter Benjamin, Deleuze and Guattari, David Foster Wallace; Sigmund Freud; miniaturization, animalism, asceticism, children, food, knife, machine; Charlie Chaplin, Benito Mussolini